Stories Unheard: The Lived Experience of Parents with Hard of Hearing Children - Yu, Franzys Kaylie V. (Technium Social Sciences Journal, 2026)
An increasing number of children with hearing loss are born to hearing parents. Learning about the diagnosis of their children often evokes strong emotions from parents including confusion, sadness, and apprehension due to their lack of prior experience in raising hard of hearing children or using sign language to communicate with them. As a result, this creates a challenging situation where parents must navigate. The objective of this study was to delve into the lived experiences of parents with hard of hearing children. Therefore, this study utilized qualitative research using a phenomenological approach. Through in-depth interviews, data were collected from seven parents with hard of hearing children who were identified through purposive sampling. Furthermore, four major themes emerged from this study namely: (1) A Bend in the Road: Navigating the Unexpected Parental Journey, (2) The Longest Ride: The Journey of Parenting a Hard of Hearing Child, (3) The Best of Me: The Resilient Parent, and (4) Dreamland: Pursuit of Dreams and Aspirations. The following are the subthemes: (1) The Rescue: Navigating Assistive Devices, (2) The Choice: Choosing the Best Option for the Child, (3) Message in a Bottle: Communication and Its Complexities, (4) See Me: Dealing with Unkind Treatment, (5) The Guardian: I Protect the Family, (6) Counting Miracles: Journey Towards Acceptance, (7) True Believer: Anchored in Faith, and (8) Safe Haven: Seeking and Receiving Support. Findings of this study contributes to the existing body of knowledge on the lived experiences of parents with hard of hearing children.